Analysis Of Vendor Income After The Traditional Market Revitalization Policy (Case Study: Simpang Market, Srimenanti, East Lampung Regency) - Ferdi Galang Bonanza; Emi Maimunah (Cita konsultindo, 2024)
This study investigates the differences in traders' income, number of customers, and retribution fees between before and after the market revitalization policy. Through a quantitative approach and data collection from relevant informants, followed by the Wilxocon signed rank test, the study found that the market revitalization policy led to a negative difference, namely a decrease in the income and number of consumers of market traders, as well as an increase in retribution costs after the market revitalization policy.